An Analysis of College Entrance Test - Anni Fazlina (English Education Journal, 2018)
This research is aimed at analyzing the quality of entrance test conducted by STKIP Bina Bangsa Getsempena year 2016-2017 in terms of validity, reliability, difficulty index, discrimination index, and the effectiveness of distractors. Content analysis was employed as research method in this study. Document analysis is a technique carried out to collect the data. The objects of this study were 25 multiple-choice items used in entrance test, with five options for each item. The data were analyzed manually. The result showed that English entrance test of STKIP Bina Bangsa Getsempena year 2016-2017 has a low predictive validity with correlation coefficient 0.044. Secondly, the r-value was 0.664, which is higher than r-table = 0.396. It is considered that the test has good reliability. Thirdly, the difficulty index was obtained that 4% of the test was easy with index 0.71-1.00, 64% was moderate with index 0.31-0.71, and 32% was difficult with index 0.00-0.31. Fourthly, most of items considered has perfect discrimination index, with the percentage is 84%, while there were also 4% with zero discriminaton and 12% with negative discrimination. Finally, 97% of distractors of STKIP Bina Bangsa Getsempena English entrance test were effective since they were chosen by more than 5% of the whole participants. There were 3% distractors that were considered ineffective as they were chosen by less than 5% of the whole participants. It means that the items in STKIP Bina Bangsa Getsempena English entrance test particularly in their difficulty index, discrimination index, and effectiveness of distractors are needed to be revised if the items will be used in next years’ entrance test.